Characterization of Biofilm Formation by Mycobacterium chimaera on Medical Device Materials - Siddam, Archana D.; Zaslow, Shari J.; Wang, Yi; Phillips, K. Scott; Silverman, Matthew D.; Regan, Patrick M.; Amarasinghe, Jayaleka J. (Frontiers in Microbiology, 2021)
Non-tuberculous mycobacteria (NTM) are widespread in the environment and are a public health concern due to their resistance to antimicrobial agents. The colonization of surgical heater-cooler devices (HCDs) by the slow-growing NTM species Mycobacterium chimaera has recently been linked to multiple invasive infections in patients worldwide. The resistance of M. chimaera to antimicrobials may be aided by a protective biofilm matrix of extracellular polymeric substances (EPS). This study explored the hypothesis that M. chimaera can form biofilms on medically relevant materials. Several M. chimaera strains, including two HCD isolates, were used to inoculate a panel of medical device materials. M. chimaera colonization of the surfaces was monitored for 6 weeks. M. chimaera formed a robust biofilm at the air-liquid interface of borosilicate glass tubes, which increased in mass over time. M. chimaera was observed by 3D Laser Scanning Microscopy to have motility during colonization, and form biofilms on stainless steel, titanium, silicone and polystyrene surfaces during the first week of inoculation. Scanning electron microscopy (SEM) of M. chimaera biofilms after 4 weeks of inoculation showed that M. chimaera cells were enclosed entirely in extracellular material, while cryo-preserved SEM samples further revealed that an ultrastructural component of the EPS matrix was a tangled mesh of 3D fiber-like projections connecting cells. Considering that slow-growing M. chimaera typically has culture times on the order of weeks, the microscopically observed ability to rapidly colonize stainless steel and titanium surfaces in as little as 24 h after inoculation is uncharacteristic. The insights that this study provides into M. chimaera colonization and biofilm formation of medical device materials are a significant advance in our fundamental understanding of M. chimaera surface interactions and have important implications for research into novel antimicrobial materials, designs and other approaches to help reduce the risk of infection.